Semantic Data Extraction. (2015) - Jánosi-Rancz, Katalin Tünde; Lajos, Árpád
Abstract: Data extractors are generally difficult to maintain. To simplify the difficult tasks of integrating new data sources and of handling structural changes within existing data sources, we have implemented a new approach called RK . RK is a tool which serves as a guide for extraction purposes; the semantic tree generated by the semantic rules (used as input), describes a pattern that represents the structure of the data source. Our system supports data extraction from hierarchical-structured data sources. Results of experiments using the RK tool have proved the feasibility of our approach by enhancing extraction in terms of precision and speed.